2015
DOI: 10.1073/pnas.1422340112
|View full text |Cite
|
Sign up to set email alerts
|

Cas9-mediated targeting of viral RNA in eukaryotic cells

Abstract: SignificanceThe clustered, regularly interspaced, short palindromic repeats associated endonuclease, Cas9, has quickly become a revolutionary tool in genome engineering. Utilizing small guiding RNAs, Cas9 can be targeted to specific DNA sequences of interest, where it catalyzes DNA cleavage. We now demonstrate that Cas9 from the Gram-negative bacterium Francisella novicida (FnCas9) can be reprogrammed to target a specific RNA substrate, the genome of the +ssRNA virus, hepatitis C virus, in eukaryotic cells. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 234 publications
(160 citation statements)
references
References 36 publications
1
159
0
Order By: Relevance
“…It will be interesting to see whether sgRNA-Cas9 nickases can be programmed to cut singlestranded RNAs by RNA interference (RNAi). It has been shown that Cas9 endonuclease from Francisella novicida (FnCas9) in complex with sgRNA can be used to target (+) strand ss-viral RNA and hepatitis C virus RNA and inhibit viral replication (93). Thermus thermopilus type III-B CRISPR-Cas systems exclusively target ssRNA for degradation and not DNA sequences that are complementary to the crRNA [reviewed in (76)].…”
Section: With Nicking Enzymes Guided By Rnamentioning
confidence: 99%
“…It will be interesting to see whether sgRNA-Cas9 nickases can be programmed to cut singlestranded RNAs by RNA interference (RNAi). It has been shown that Cas9 endonuclease from Francisella novicida (FnCas9) in complex with sgRNA can be used to target (+) strand ss-viral RNA and hepatitis C virus RNA and inhibit viral replication (93). Thermus thermopilus type III-B CRISPR-Cas systems exclusively target ssRNA for degradation and not DNA sequences that are complementary to the crRNA [reviewed in (76)].…”
Section: With Nicking Enzymes Guided By Rnamentioning
confidence: 99%
“…FnCas9 was recently used to target the genome of the positive sense single-stranded RNA (+ssRNA) virus, hepatitis C virus (HCV), as a proof of principle [102]. HCV is an important human pathogen that can cause liver fibrosis, cirrhosis, and may lead to hepatocellular carcinoma [103].…”
Section: Cas9 Targeting Of Rnamentioning
confidence: 99%
“…Similarly, in human induced pluripotent stem cells (iPSCs) derived from a myeloproliferative neoplasm, Cas9 was used to repair the oncogenic mutation (Smith et al 2015), and mutations in the crygc gene that is responsible for cataracts were repaired in mouse zygotes and spermatogonial stem cells (Ren et al 2013; Wu et al 2015). Additionally, HIV proviruses have been removed from infected cells using Cas9-directed cleavage, and hepatitis B and hepatitis C viruses have been targeted, perhaps providing a framework for future antiviral therapeutics (Hu et al 2014; Lin et al 2014a; Kennedy et al 2015; Liao et al 2015; Price et al 2015). Such repair has not been limited to tissue culture studies ex vivo.…”
Section: Use Of Cas9 For Genome Engineeringmentioning
confidence: 99%